Program Layanan Konsultasi Psikologis pada Penyintas Long Covid-19 - Diny Amenike; Egha Febrianingsih; Sylvia Dewiriza; Haznaz Dhiya Ulhaq Z.N.; Cikita Aidha Putri; Rozi Sastra Purna; Dwi Puspasari; Septi Mayang Sarry; Nila Anggreiny; Meria Susanti; Amatul Firdausa Nasa; Siska Oktari; Yantri Maputra; Tri Rahayuningsih; Fitria Rahmi; Mafaza Mafaza; Izzanil Hidayati; Liliyana Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Survivors of Covid-19 can still experience symptoms such as being still infected with a virus known as Long Covid-19. Covid-19 survivors with long Covid-19 experience physical and psychological disorders. Psychological disorders include cognitive disorders, memory loss, anxiety, sleep disorders, quality of life disorders, and work problems. This problem will undoubtedly impact individual productivity, so it is necessary to carry out a